1999
DOI: 10.1093/ajcp/112.5.657
|View full text |Cite
|
Sign up to set email alerts
|

Performance Characteristics of Three Serum Iron and Total Iron-Binding Capacity Methods in Acute Iron Overdose

Abstract: A b s t r a c tAccurate serum iron and total iron binding capacity (TIBC)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…Measurement of transferrin is the preferred test (1 mol of transferrin binds 2 mol of iron). If this test is not available, direct UIBC assays are less susceptible to falsely high results attributable to iron overdose (92 ). Some patients with an iron overdose are treated with deferoxamine.…”
Section: E Testing For Iron Toxicitymentioning
confidence: 99%
“…Measurement of transferrin is the preferred test (1 mol of transferrin binds 2 mol of iron). If this test is not available, direct UIBC assays are less susceptible to falsely high results attributable to iron overdose (92 ). Some patients with an iron overdose are treated with deferoxamine.…”
Section: E Testing For Iron Toxicitymentioning
confidence: 99%
“…On the other hand, DFX-Fe measurement of sFe was certainly influenced by [17,18]. Although there should be differences in the biological behavior of DFO and DFX, our present results indicated that careful attention should be paid when these markers are observed during iron chelation therapy with DFX.…”
Section: Discussionmentioning
confidence: 56%
“…The total iron-binding capacity (TIBC) is to measure the concentration of transferrin of serum because the free iron binds with some proteins. Low TIBC causes inflammatory disorders (Feldman et al, 1981;Ottenjann et al, 2006;Smith and Cipriano, 1987;White et al, 2012), while its increased level indicates due to excess iron overload (Kasvosve and Delanghe, 2002;Moosavian et al, 2010;Roberts et al, 1999) if patients with chronic hepatopathy (Jacobs et al, 2000). Production of antioxidants could be function for the prevention of proteolysis by accommodating the free cations including iron.…”
Section: Resultsmentioning
confidence: 99%